2001
DOI: 10.1017/s0305000901004676
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary development in Italian children: a longitudinal evaluation of quantitative and qualitative aspects

Abstract: In this study vocabulary development of a sample of 42 Italian children was evaluated through monthly administration of the Italian version of the CDI. Data collection started at 1;0–1;1 for 32 children and at 1;3–1;4 for the remaining subjects and continued until children’s vocabulary reached 200 words. At fixed stages of vocabulary size (50, 100 and 200 words), individual differences in percentile scores and vocabulary composition were examined. Individual growth curves were analysed in order to verify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
2
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 0 publications
13
69
2
11
Order By: Relevance
“…Also consistent with Bornstein et al (2004), D'Odorico, Carubbi, Salerni & Calvo (2001 found that noun predominance varied with vocabulary size and that there were marked individual differences in noun predominance. In contrast, there is some evidence that children learning Mandarin, Korean and Dutch do not show a strong predominance of nouns in their early vocabularies (Tardif, 1996 ;Tomasello & Merriman, 1995).…”
Section: Cross-linguistic CDI Findingssupporting
confidence: 88%
“…Also consistent with Bornstein et al (2004), D'Odorico, Carubbi, Salerni & Calvo (2001 found that noun predominance varied with vocabulary size and that there were marked individual differences in noun predominance. In contrast, there is some evidence that children learning Mandarin, Korean and Dutch do not show a strong predominance of nouns in their early vocabularies (Tardif, 1996 ;Tomasello & Merriman, 1995).…”
Section: Cross-linguistic CDI Findingssupporting
confidence: 88%
“…International studies confirm that, after a small vocabulary growth approximately from 12 to 24 months of age, the child goes through a period called vocabulary explosion, demonstrating the age effect over the produced lexical items, in the same manner that occurred in the current study [27][28][29][30] . Still related to the age group, the data found here confirm an international study in which it places the rising of grammatical words as slow 30 , since there was a certain content word predominance.…”
Section: Resultssupporting
confidence: 81%
“…Most studies find the same order of acquisition as is found for English: Children learn nouns more easily than predicates Caselli, Casadio, & Bates, 1999;D'Amico, Devescovi, & Bates, 2003;D'Odorico, Carubbi, Salerni, & Calvo, 2001). However, Camaioni and Longobardi (1995) observed the speech production of 15 children in the age range of 16-20 months and found that only 1 child showed a clear predominance of nouns.…”
Section: Nouns Verbs and Adjectivesmentioning
confidence: 70%
“…Therefore, whereas very young children (up to 30 months of age) use mostly very imageable words, subsequent lexical choices and/or the types of subjects treated cause an increased incidence of less imageable words, and this holds specifically for verbs. When we split words of the CFV by grammatical category, we obtained additional data favoring the theory of the evolutionary sequence of vocabulary acquisition (see Caselli et al, 1999;Colombo & Burani, 2002;D'Amico et al, 2003;D'Odorico et al, 2001;Szekely et al, in press). Like children in other countries, Italian children seem to acquire nouns earlier and more easily than predicates (i.e., verbs and adjectives).…”
Section: Discussionmentioning
confidence: 82%